Female obesity and infertility: A Narrative Literature Review: Obesidad e Infertilidad Femenina: Una Revisión Narrativa - Domínguez-Tenesaca , Sandra Maribel (2024)
Obesity is associated with various adverse maternal and fetal effects prenatally, but can also cause infertility. Adipose tissue through the production of many factors, such as leptin, free fatty acids (FFA) and cytokines, can affect the functions of both the ovary and the maturation of oocytes and the receptivity of the endometrial epithelium. Reducing obesity improves women's reproductive health. The objective of this study is to update documentation on female obesity and infertility. Methods: It was a review of the literature. The scientific search was carried out in databases such as Scopuss, Pudmed, Scielo, and in indexed and impact journals, using descriptors in English such as And, Or, In among others, the inclusion and exclusion criteria were taken into account for select from each database. Results: 70 articles were found, of which 40 were left that were eligible. These were mostly original, quantitative research, carried out with surveys, with logistic regression, published within the last 5 years. Conclusions: Obesity may contribute to ovulation problems and irregular menstrual periods. It also contributes to a lower response to infertility treatments and spontaneous abortions.